417 - Comparison of prevalence and disturbance of neuropsychic symptoms between institution-dwelling and community-dwelling patients with dementia. (October 2021) - Lu, Xuejiao; Wu, Jialan; Ye, Rui; Liao, Xiaoyan
Abstract: Objectives: To explore differences in prevalence and disturbance of behavioral and psychological symptoms of dementia (BPSD) between institution-dwelling and community-dwelling patients with dementia. Methods: A cross-sectional survey was conducted. Institution-dwelling (n=112) and community-dwelling patients with dementia (n=157) were enrolled from a nursing home and a tertiary psychiatric hospital located in Guangzhou, China, from March 2019 to September 2019. Neuropsychiatric Inventory (NPI) was used to assess the prevalence and disturbance of BPSDs. Results: The community-dwelling patients were older, and having more antianxiety, anticonvulsant, anti- depression, anti-dementia medication use than institution-dwelling patients, while institution-dwelling patients used more antipsychotics than community-dwelling patients. The prevalence of hallucinations (χ 2 = 8.55, P = 0.004), agitation (χ 2 = 5.38, P = 0.026), depression (χ 2 = 22.78, P < 0.001), anxiety (χ 2 = 47.17, P < 0.001), aberrant motor behavior (χ 2 = 4.72, P = 0.034), and sleep (χ 2 = 4.16, P = 0.047) was higher in community-dwelling patients than that in institution-dwelling patients. Moreover, the frequency, severity, and disturbance of almost all of the BPSDs were higher in community-dwelling patients than those in institution-dwelling patients, except for euphoria. High Odds of having hallucination (OR 2.48, 95% CI 1.37-4.49), anxiety (OR 7.36, 95% CI 3.82-14.17), sleep disorder (OR 1.77, 95% CI 1.02-3.10) was observed in community-dwelling patients. Severe dementia was another risk factor for having hallucination (OR 5.48, 95% CI 2.25-13.38), anxiety (OR 2.73, 95% CI 1.22-6.12), sleep disorder (OR 2.61, 95% CI 1.21-5.64), apathy (OR 3.03, 95% CI 1.49-6.19), and irritability (OR 2.6, 95% CI 1.24-5.51). Community-dwelling and severe dementia were two main risk factors for higher NPI scores (adjusted R 2 = 0.30), and higher disturbance of anxiety (adjusted R 2 = 0.21), sleep disorders (adjusted R 2 = 0.15), hallucination (adjusted R 2 = 0.12) and irritability (adjusted R 2 = 0.11). Conclusion: The prevalence and disturbance of BPSDs were higher in community-dwelling patients with dementia than institution-dwelling patients. Community-dwelling and severe dementia were two main risk factors for higher prevalence and disturbance of BPSDs, especially for anxiety, sleep disorders, and hallucination. Providing community-based BPSDs coping skill training and support for informal caregivers are needed.